HUBUNGAN MAKNA HIDUP DAN QUARTER LIFE CRISIS PADA GENERASI Z YATIM/PIATU - Jolanda Chatarina Wibawa; Riana Sahrani (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Quarter life crisis is one of the developmental challenges commonly experienced by Generation Z, particularly among individuals who face psychological vulnerability due to parental loss. However, studies examining psychological factors associated with quarter life crisis among Generation Z individuals who have lost one or both parents remain limited. This study aimed to examine the relationship between meaning in life and quarter life crisis among Generation Z individuals who had lost one or both parents. This study employed a quantitative approach with a correlational design. The participants were 392 Generation Z individuals who had lost one or both parents, recruited using purposive sampling. Data were collected using the Meaning in Life Questionnaire (MLQ) and the Quarter Life Crisis Scale (QLCS). The data were analyzed using Spearman’s rho correlation. The results showed a significant negative relationship between meaning in life and quarter life crisis (rs = -0.546, p < .001). These findings indicate that higher meaning in life was associated with lower quarter life crisis among bereaved Generation Z individuals. The findings suggest that meaning in life is related to more adaptive psychological functioning in this group. This study may serve as a basis for developing psychological interventions focused on strengthening meaning in life among vulnerable populations. ABSTRAK Quarter life crisis merupakan salah satu tantangan perkembangan yang sering dialami Generasi Z, terutama pada individu yang menghadapi kerentanan psikologis akibat kehilangan orang tua. Namun, penelitian mengenai faktor psikologis yang berkaitan dengan quarter life crisis pada Generasi Z yatim/piatu masih terbatas. Penelitian ini bertujuan untuk menguji hubungan antara makna hidup dan quarter life crisis pada Generasi Z yatim/piatu. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Partisipan penelitian berjumlah 392 individu Generasi Z yang kehilangan satu atau kedua orang tua, yang diperoleh melalui teknik purposive sampling. Data dikumpulkan menggunakan Meaning in Life Questionnaire (MLQ) dan Quarter Life Crisis Scale (QLCS). Analisis data dilakukan dengan uji korelasi Spearman’s rho. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara makna hidup dan quarter life crisis (rs = -0.546, p < 0.001). Temuan ini menunjukkan bahwa semakin tinggi makna hidup, semakin rendah quarter life crisis pada Generasi Z yatim/piatu. Hasil ini mengindikasikan bahwa makna hidup berkaitan dengan kondisi psikologis yang lebih adaptif pada kelompok tersebut. Penelitian ini diharapkan dapat menjadi dasar bagi pengembangan intervensi psikologis yang berfokus pada penguatan makna hidup pada kelompok rentan.